Emigrar: Vale la Pena - Pablo Marcos Martin (Maya America, 2020)
In this short but comprehensive essay where prose bridges poetry, Pablo Marcos Martin summarizes the immigrant experience in six steps, and reveals the multiple characteristics and the multiple outcomes of the immigration experience. Originally published in 2006, this essay remains profoundly pertinent to the study of survival migration, including family separation, the journey to the border, consequences of choice and circumstance, and the possibilities for failure as well as for happiness.